(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2020)
Background: Maternal death in pregnancy may not reflect the scale of acute morbidities associated with pregnancy and childbirth. Studying cases of women who survived a severe complication in pregnancy, childbirth on the post partum period (Maternal near miss) is increasingly being recognized as potentially more useful then studying maternal mortality in terms of assessing healthcare needs. To determine the causes of maternal near miss. Maternal Near Miss incidence ratio. Maternal near miss to mortality ratio and mortality index. Materials and methods : A prospective cross sectional study was performed from January 2015- December 2015 at a tertiary care hospital in Chattogram. All women admitted to study facilities with pregnancy related complications or for birth. An adopted version of the WHO Maternal Near Miss Screening Tools was used to identify Maternal Near Miss cases. Incidence of maternal near miss, Maternal Near Miss to maternal mortality ratio and causes of and factors associated with Maternal Near Miss. Results : There were 3089 deliveries, 90 near miss cases during the study period. The maternal near miss incidence ratio was 31.4/1000 live births, maternal near miss to mortality ratio was 5:1 and mortality index was 16.7%. Eclampsia (35.6%) was the leading causes of near miss, followed by haemorrhage (23.3%) and ruptured uterus (11.1%). Conclusion : The Near Miss rate was high. Contributing factors were lack of resources, low quality of primary health care and delays in care. All Near Miss should be accepted as opportunities to improve the quality of maternity care. Health sector should address delays in conducting intervention, referral barriers and fully equipped intensive care units must be created in all facilities. JCMCTA 2019 ; 30 (2) : 32-35